Impact of health education intervention on breast cancer awareness among rural women of Tamil Nadu - B Nisha; Ramachandran Murali (Wolters Kluwer Medknow Publications, 2020)
Background: The most common cancer among Indian females is breast cancer. Limited access to early detection and treatment is responsible for more than half of the deaths, primarily in rural areas, where organized mammography screening is neither affordable nor feasible. Therefore, imparting awareness on breast health and breast self-examination (BSE) is highly recommended. This study aimed to assess the impact of a health education interventional program on breast health awareness and BSE among rural women of Tamil Nadu. Methodology: A quasi-experimental study was conducted among 266 women. A preinterventional survey was done using a pretested validated questionnaire. A multipronged breast health education intervention was administered and its effectiveness was measured after 3 months using the same tool. Results: There was a statistically significant (P = 0.0001) improvement in the knowledge of breast health, perceived susceptibility, and reasons for practice and proficiency of BSE practice of the interventional group from pre- to post-test. After the interventional program, 71.8% of increase in knowledge about breast health and BSE was observed. In addition, 64.7% of the women practiced BSE compared to 7.14% pretest. Conclusion: This study highlights the awareness needs by the women and application of extensive strategies to increase the acceptance of cancer screening programs.